Development of the postgraduate pedagogical education of bukovina of the first half of the XX century - Tsybaniuk, Oleksandra (ScienceRise: Pedagogical Education, 2020)
The need for professional staff in the territory of Bukovina appeared immediately at the time of the formation of the system of physical education of students in the mid-nineteenth century. In the content of the «Organizational of High Schools and Real Schools in the Austro-Hungarian Empire», the law of May 14, 1869 declared the official recognition of «physical exercises» as a compulsory subject of teaching. In addition, the decree of the Minister of Religion and Education on the requirements for the procedure for admission of state exams to candidates for the post of teacher of gymnastics (1870) played an important role in the staffing of the system of physical education of Bukovina. It was the lack of professional staff that made public activists to organize various forms of training of gymnastics teachers, general physical training instructors. «Gymnastics-fire» courses, in which popularization the Bukovina press actively participated, were systematically held in the capital of the region. At the request of the system of physical education of all segments of the population of Bukovina in the region, a procedure for training and advanced training of specialists in this field was established. But to combine all forms of advanced training into a single state system, to create an institution that meets the requirements of time, pedagogical provisions became possible only in 40's of the twentieth century. The period of 1938-1939 was the stage of the formation of a system of methodical work with the managerial and pedagogical staff of education of the USSR. The main components of this became: school, shrub methodical associations, pedagogical offices at district departments of public education, institutes of teacher improvement at regional departments of public education. The Institute consisted of nine teaching and training offices, including: pedagogy, elementary classes, Ukrainian and Russian language and literature, foreign languages, history and geography, mathematics and physics, biology and chemistry, physical education, extracurricular education